Solid lipid nanoparticles in pancreatic cancer treatment - Mia Dunn; Lewis Dymock; Clare Hoskins (BJC Reports)
Abstract Pancreatic cancer comes with one of the poorest prognoses of all cancers and as such it is crucial that new therapies are developed to improve on the current statistics. Currently, chemotherapy is the cornerstone of pancreatic cancer treatment with several drugs, and combinations of drugs being utilised for their anti-cancer effect. However, pancreatic cancer has a dense stroma around the tumour and intratumoral bacteria which result in drugs having difficulty penetrating the tumour or being metabolised by bacteria rendering them inactive. The utilisation of nanotechnology in chemotherapy for pancreatic cancer has been a huge area of focus for researchers worldwide with most of the focus being on lipid-based, inorganic and polymer-based nanoparticles. Solid lipid nanoparticles which have been studied since being first published in the 1990s, have been poorly researched for pancreatic cancer applications. Being composed of physiological lipids, solid lipid nanoparticles offer a greatly reduced risk of acute or chronic toxicities arising compared to inorganic or polymeric nanoparticles. They also possess the ability to improve on circulation time, permeability, and bioavailability of many first-line chemotherapeutics.